Why there is no dilemma for the birth strategy: a response to Bobier and Omelianchuk - Singh, Prabhpal (Journal of medical ethics, 2023)
Bobier and Omelianchuk argue that the Birth Strategy for addressing analogies between abortion and infanticide is saddled with a dilemma. It must be accepted that non-therapeutic late-term abortions are either, impermissible, or they are not. If accepted, then the Birth Strategy is undermined. If not, then the highly unintuitive claim that non-therapeutic late-term abortions are permissible must be accepted. I argue that the moral principle employed to defend the claim that non-therapeutic late-term abortions are morally impermissible fails to do so. Furthermore, the principle that people have a right to bodily autonomy can be used as an argument for the conclusion that non-therapeutic late-term abortions are permissible and is intuitively stronger than the intuition for the opposite of this conclusion. This is because people having a right to bodily autonomy explains the impermissibility of rape and sexual assault. Consequently, the posited dilemma is defused and does not undermine the Birth Strategy.